Physical activity limitations in children with severe hemophilia A. does emicizumab make a difference? - Ahmed Sobhi Hassan; Laila Metwally Sherief; Mona Hamdy; Abeer Salamah; Osama A El-Agamy (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the effect of emicizumab on physical activity in children with severe haemophilia A. Method: The prospective cohort study was conducted from October 2021 to April 2022 at the Paediatric Department of Kafrelsheikh University Hospital, Egypt, in collaboration with the Haematology out-patient clinic of the Paediatric Department, Zagazig University, Egypt, and the Paediatric Department of Cairo University Hospital, Egypt, and comprised children aged 4-18 years with severe haemophilia A who received emicizumab prophylaxis. Paediatric Haemophilia Activities List was used to assess physical activity at baseline and after six months of regular emicizumab prophylaxis. Data was analysed using SPSS 26. Results: There were 29 children, all (100%) boys, with mean age 8.7±3.51 years (range 4-15 years. Of them, 17(58.62%) patients were negative for inhibitors. Median Paediatric Haemophilia Activities List sum score was 59.54 (interquartile range: 50.15-62.05) at baseline which moved up to 84 (interquartile range: 79.05-86.35) post-intervention (p<0.001). Conclusion: Emicizumab prophylaxis improved the level of physical activity in children with severe haemophilia A. Keywords: Emicizumab, Haemophilia, Haematology, PedHAL.